DETERMINANTS OF THE NATIONAL HEALTH INSURANCE UPTAKE IN INDONESIA - Abdu Nafan Aisul Muhlis (Universitas Airlangga, 2022)
Background: Indonesia introduced a national health insurance program, the so-called Jaminan Kesehatan National (JKN), in 2014 to enhance health access for its citizens. However, unattained universal health coverage (UHC) such as participation target becomes a concern. Aims: This study aimed to examine the factors influencing JKN participation and propose a possible policy improvement to enhance UHC implementation Methods: A systematic review was performed based on PRISMA guidelines, and literature was collected from PubMed, Scopus, Web of Science, Cochrane Library, and Google Search. Results: 21 articles in English and Indonesian language are included in the study after being reviewed using the PRISMA flowchart and quality assessment. The main factors that emerged from the found literature affecting the low enrolment of the NHIS include socio-demographic factors: younger people, low education level, rural location, unstable incomes, and larger family members. Also, health-related, and other factors: lack of health insurance literacy, insufficient healthcare accessibility and services availability, inadequate healthcare service quality, complicated administrative procedure, negative stigma, membership data inaccuracy, and low health status. Conclusion: Twelve factors have been identified as the most influential determinants for the national health insurance program. Some proposed policies derived from the current results might contribute to the attainment of UHC.